2015
DOI: 10.5545/sv-jme.2015.2818
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Effect of the Reynolds Numbers on Thermal and Hydrodynamic Parameters of Turbulent Flow Mixed Convection Heat Transfer in an Inclined Tube

Abstract: A numerical investigation of the effect of the Reynolds number on the thermal and hydrodynamic parameters of mixed convection heat transfer of the water-Al 2 O 3 nanofluid turbulent flow in an inclined circular channel is the subject of this article. The upper wall of the channel was under non-uniform heat flux and its lower part was isolated. The two-phase mixture model, the finite volume method, and the secondorder upstream difference scheme were used to solve the governing equations. After reviewing the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…Case 1 has the smallest inner diameter of absorber tube so the oil velocity in the tube was greatest, and the flow became more turbulent. This simulation result has a good agreement with the study by Vahidinia and Miri [23] where they reported that the thermal performance in turbulent pipe flow rises with increasing Reynolds number since the heat transfer coefficient increases with the increase of the Reynolds number. Therefore, it is determined that the HCE size of Case 1 is appropriate for the PTC.…”
Section: Sizing Of the Ptcsupporting
confidence: 90%
“…Case 1 has the smallest inner diameter of absorber tube so the oil velocity in the tube was greatest, and the flow became more turbulent. This simulation result has a good agreement with the study by Vahidinia and Miri [23] where they reported that the thermal performance in turbulent pipe flow rises with increasing Reynolds number since the heat transfer coefficient increases with the increase of the Reynolds number. Therefore, it is determined that the HCE size of Case 1 is appropriate for the PTC.…”
Section: Sizing Of the Ptcsupporting
confidence: 90%
“…4. The trend suggests that Nu increases linearly with Re as reported in the literature for different heat exchangers [29][30][31] but in each case the slopes varies due to different geometric and flow conditions. Hot inlet temperature in each experiment was kept constant at about 25°C in all experiments but we also checked it for some other values and the correlation developed was not affected by changing its value.…”
Section: Resultssupporting
confidence: 74%
“…Thermophoresis is a phenomenon by which the nanoparticles in the base fluid will be thrusted from hotter to the colder region due to the temperature gradient exists in the fluid. Thermophoretic velocity of nanoparticles accounts all the three aforesaid parameters, and it can be estimated through the thermophoretic mobility of nanoparticles [21] as given in Equation ( 7):…”
Section: Solutionmentioning
confidence: 99%